Understanding mobile banking adoption via the technology acceptance model: evidence from Jordan - Bara Waleed Rababa; Azwadi Ali; Al Montaser Mohammad (Banks and Bank Systems)
This paper studies the use of mobile banking in Jordan and the factors affecting its adoption through the Technology Acceptance Model (TAM). It examines user behavior across new banking technologies and resistance to adoption, focusing on factors such as perceived ease of use, usefulness, cost, social influence, and trust. The study employed convenience sampling because of privacy restrictions and the lack of a reliable customer database. 498 individuals completed a structured questionnaire, and 437 of them provided valid answers (87.8%). Using a 5-point Likert scale, the questionnaire evaluated demographic information and opinions about the adoption of mobile banking. The responses were analyzed using SmartPLS software. The results reveal that perceived usefulness is a key predictor of the willingness of the Jordanian population to adopt mobile banking. Perceived risk also positively impacts mobile banking usage, while perceived ease of use presents a moderate but significant barrier to adoption. Perceived ease of use also has a significant influence on perceived usefulness, which mediates its effect on adoption. While social influence plays an important role in adopting mobile banking services, trust does not directly affect the intention to use these services.